Optical Characterization of Coastal Waters with Atmospheric Correction Errors: Insights from SGLI and AERONET-OC - Hiroto Higa; Masataka Muto; Salem Ibrahim Salem; Hiroshi Kobayashi; Joji Ishizaka; Kazunori Ogata; Mitsuhiro Toratani; Kuniaki Takahashi; Fabrice Maupin; Stephane Victori (Remote Sensing)
This study identifies the characteristics of water regions with negative normalized water-leaving radiance (<semantics>nLw(λ)</semantics>) values in the satellite observations of the Second-generation Global Imager (SGLI) sensor aboard the Global Change Observation Mission–Climate (GCOM-C) satellite. SGLI Level-2 data, along with atmospheric and in-water optical properties measured by the sun photometers in the AErosol RObotic NETwork-Ocean Color (AERONET-OC) from 26 sites globally, are utilized in this study. The focus is particularly on Tokyo Bay and the Ariake Sea, semi-enclosed water regions in Japan where previous research has pointed out the occurrence of negative <semantics>nLw(λ)</semantics> values due to atmospheric correction with SGLI. The study examines the temporal changes in atmospheric and in-water optical properties in these two regions, and identifies the characteristics of regions prone to negative <semantics>nLw(λ)</semantics> values due to atmospheric correction by comparing the optical properties of these regions with those of 24 other AERONET-OC sites. The time series results of <semantics>nLw(λ)</semantics> and the single-scattering albedo (<semantics>ω(λ)</semantics>) obtained by the sun photometers at the two sites in Tokyo Bay and Ariake Sea, along with SGLI <semantics>nLw(λ)</semantics>, indicate the occurrence of negative values in SGLI <semantics>nLw(λ)</semantics> in blue band regions, which are mainly attributed to the inflow of absorptive aerosols. However, these negative values are not entirely explained by <semantics>ω(λ)</semantics> at 443 nm alone. Additionally, a comparison of in situ <semantics>nLw(λ)</semantics> measurements in Tokyo Bay and the Ariake Sea with <semantics>nLw(λ)</semantics> values obtained from 24 other AERONET-OC sites, as well as the inherent optical properties (IOPs) estimated through the Quasi-Analytical Algorithm version 5 (QAA_v5), identified five sites—Gulf of Riga, Long Island Sound, Lake Vanern, the Tokyo Bay, and Ariake Sea—as regions where negative <semantics>nLw(λ)</semantics> values are more likely to occur. These regions also tend to have lower <semantics>nLw(λ) </semantics> values at shorter wavelengths. Furthermore, relatively high light absorption by phytoplankton and colored dissolved organic matter, plus non-algal particles, was confirmed in these regions. This occurs because atmospheric correction processing excessively subtracts aerosol light scattering due to the influence of aerosol absorption, increasing the probability of the occurrence of negative <semantics>nLw(λ)</semantics> values. Based on the analysis of atmospheric and in-water optical measurements derived from AERONET-OC in this study, it was found that negative <semantics>nLw(λ) </semantics> values due to atmospheric correction are more likely to occur in water regions characterized by both the presence of absorptive aerosols in the atmosphere and high light absorption by in-water substances.